2014
DOI: 10.5901/mjss.2014.v5n23p742
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Finance Operations and Socio-Economic Development of Nigeria Rural Communities

Abstract: This paper focused on the role of Microfinance banks on the socio-economic development of rural communities in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…When new communities come to a country, they bring with them different cultural practices that may affect their health-seeking behaviour (Obot, 2012). The BSSA culture is very sensitive to explicit questions of a sexual nature, especially when asked by a person of the opposite sex (Ojua and Omono, 2012). This is the reason why some research participants were not comfortable with direct questions of a sexual nature.…”
Section: Discussionmentioning
confidence: 99%
“…When new communities come to a country, they bring with them different cultural practices that may affect their health-seeking behaviour (Obot, 2012). The BSSA culture is very sensitive to explicit questions of a sexual nature, especially when asked by a person of the opposite sex (Ojua and Omono, 2012). This is the reason why some research participants were not comfortable with direct questions of a sexual nature.…”
Section: Discussionmentioning
confidence: 99%
“…The seeds were grown differently according to the treatments in nursery baskets filled with topsoil mixed with poultry manure and watered daily [14]. After 6 weeks of planting, the seedlings from each treatment were transplanted into polybags filled with similar soil-manure content used in the nursery [15]. The plants were grown in the Botanical Garden of the University of Nigeria, Nsukka using a 3 x 5 factorial experimental laid out in a completely randomized design (CRD) with 10 replications for every treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that rural women in Nigeria face additional barriers to healthcare services due to their geographic isolation, lower levels of education, and low socio-economic status [4,5]. Moreover, cultural beliefs and traditional practices can significantly influence women's decision-making about healthcare utilization, often leading to reliance on traditional healers and home-based care [6].…”
Section: Introductionmentioning
confidence: 99%